2017
DOI: 10.1007/s00455-017-9833-z
|View full text |Cite
|
Sign up to set email alerts
|

Maturation Modulates Pharyngeal-Stimulus Provoked Pharyngeal and Respiratory Rhythms in Human Infants

Abstract: Pharyngeal-provocation induced aerodigestive symptoms in infants remain an enigma. Sources of pharyngeal provocation can be anterograde as with feeding, and retrograde as in gastroesophageal reflux. We determined maturational and dose-response effects of targeted pharyngeal-stimulus on frequency, stability, and magnitude of pharyngeal and respiratory waveforms during multiple pharyngeal swallowing responses in preterm-born infants when they were of full-term postmenstrual age (PMA). Eighteen infants (11 male) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
64
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(64 citation statements)
references
References 45 publications
0
64
0
Order By: Relevance
“…However, these signs, if associated with other systemic signs, can also be an exaggerated airway-sensory-pain response suggesting recruitment of more neural pathways and its effects on different muscular (somatic and esophageal) functions such as may happen during persistent cough. 16,[24][25][26]32 We noted that provocative stimulus volume is the strongest determinant of symptom prevalence as well as peristaltic reflex frequency-recruitment, irrespective of ARI severity or the composition of the stimulus (Figure 3, A and B). This finding supports that the mechano-, osmo-or chemo-sensitivity (determined using air insufflation, water infusion and apple juice infusion, respectively) of the esophageal mucosa or esophageal muscles is increasingly activated with stimulus volume increments, regardless of the ARI severity categories.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…However, these signs, if associated with other systemic signs, can also be an exaggerated airway-sensory-pain response suggesting recruitment of more neural pathways and its effects on different muscular (somatic and esophageal) functions such as may happen during persistent cough. 16,[24][25][26]32 We noted that provocative stimulus volume is the strongest determinant of symptom prevalence as well as peristaltic reflex frequency-recruitment, irrespective of ARI severity or the composition of the stimulus (Figure 3, A and B). This finding supports that the mechano-, osmo-or chemo-sensitivity (determined using air insufflation, water infusion and apple juice infusion, respectively) of the esophageal mucosa or esophageal muscles is increasingly activated with stimulus volume increments, regardless of the ARI severity categories.…”
Section: Discussionmentioning
confidence: 84%
“…Such cluster of symptoms/signs interpreted as 'troublesome symptoms of GERD' are likely to be cumulative mechanisms of aerodigestive vigilance, clearance and protection. 18,21,25,26,32 This clinical reasoning stems from the proof of concept (Figure 3) that increasing stimulus volume likely activates esophageal, supra-esophageal and extraesophageal reflexes, and therefore the occurrence of symptoms. Further studies are needed to clarify the pathophysiology in the context of chronic lung disease or neuropathology, both of which are uniquely common in preterm-born infants.…”
Section: Discussionmentioning
confidence: 99%
“…However, the actual number of apnea/bradycardia/desaturation events reported were only 0 (0–1) events per day, which were not associated with any of the esophageal sensitivity profiles. We and others have shown that these events are rarely associated with GER mechanisms and is more likely due to dysfunctional swallowing, which may be modified by maturation and stimulus volume ( 15 , 47 , 49 , 50 ).…”
Section: Discussionmentioning
confidence: 88%
“…We have previously used water perfusion manometry to study pharyngeal rhythms, UES, and esophageal peristalsis in preterm infants . However, this method is limited to one pressure sensor in the pharyngeal region.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously used water perfusion manometry to study pharyngeal rhythms, UES, and esophageal peristalsis in preterm infants. 17,18 However, this method is limited to one pressure sensor in the pharyngeal region. In adults, high-resolution manometry (HRM) techniques have made it possible to study both the regulatory and contractile functions in greater detail with the presence of multiple sensors in the pharyngeal region.…”
Section: Introductionmentioning
confidence: 99%